Feridas abertas e silêncios ensurdecedores: figurações do trauma nas personagens femininas de António Lobo Antunes - Valim, Graziele Maria (2021)
There are many general definitions of trauma, and among them, the most general and studied is that overwhelming experience of sudden or catastrophic events such as genocides, natural disasters, torture, rape, child abuse. According to Cathy Caruth (1995), trauma is a phenomenon, which is too shocking to be fully registered upon occurrence and which manifests belatedly in its repeated possession of the one who experiences it. The victims of this experience are susceptible to a routine of intrusive flashbacks, uncontrolled repetitive appearance of hallucinations and dreams of the traumatic event. However, if we think that traumatic shock becomes a register of the effects of living within contemporary society, and that shock or trauma becomes the daily sensation of the everyday life of the people, so we may say as result of exposure to varied and multiple traumatic experiences, trauma becomes chronic, complex and diffuse in our society. Reflecting on the notion of trauma, Laura Brown (1995) argues that when trauma is defined as unusual, as the result of a single event that is outside of the range of human experience, by inference, the daily of abusive situations, the private, secret, insidious traumas of women and vulnerable groups are excluded. Thus, this paper explores trauma from a psychosocial and literary perspective, with a specific focus in the ways António Lobo Antunes use the narrative to reconfigure and aestheticize the trauma suffered by the female characters who star in the novels Exortação aos Crocodilos (1999), Da natureza dos deuses (2015), Para aquela que está sentada no escuro à minha espera (2016). Our analysis of the female characters, regardless of the social class they occupy, show us women within a painful history of silence, abused, silenced, treated as things and property of men. Through the analysis of the configuration of trauma in antuniana narratives, our hypothesis is that the discourse of female characters, full of pain, are pieces of oppressed, aggressive and not assimilated experiences, which mean not only the impossibility of narrating, but traumatic memories. These memories construct itself by gaps and different layers of violence, and depend on the reader to assemble the pieces and complete the story. In this context, it was carried a qualitative research, descriptive, bibliographic and exploratory, this thesis takes the position that in the narratives selected here as the corpus of our research, the trauma is not represented as content or theme but within aesthetic tools that deliberately textualizing and drawing attention to the processes of memory and for a rupture of the symbolic order. In face of the novels of António Lobo Antunes, burned by pain and suffering, the reader is confronted by past and forced reflecting which was repressed or “forgotten”, with wounds that have not yet been (historically) understood